Effects of Oral Intervention on Fluctuations in Exchange Rates: Evidence from Japan 1995-2011 - Sakata, Shun; Takeda, Fumiko (Journal of Reviews on Global Economics, 2013)
Abstract: This paper studies the effects of oral interventions on the JPY/USD rate between 1995 and 2011. Traditionally, monetary authorities have intervened directly in foreign exchange markets. In recent years, however, actual interventions have been supplemented or supplanted by â€œoral interventionsâ€ to influence market expectations. In the Japanese case, monetary authorities did not directly intervene in the market from 2005 to August 2010. They conducted actual interventions only five times between 2010 and 2012, though Japan has been noted for ongoing oral intervention in recent years. Prior studies examining the impact of oral interventions provide mixed results regarding their effectiveness. Our study attempts to contribute to the literature by focusing not only on the speaker of oral interventions, but also on the content of the statements released. Using the event study methodology, we find that market participants give great credence to announcements by monetary authorities that strike a decidedly positive or negative tone about current exchange rates. In addition, market participants give great credence to statements by speakers who actually conduct exchange rate policy, including staff from the Ministry of Finance and people affiliated with the Bank of Japan.